Hierarchical graphene oxide-Ni3S2 quantum dots nanocomposites modified glassy carbon electrode for electrochemical detection of dopamine and tyrosine - Annapragada, Ratnamala; Mohammad, Haseena; Mohammad, Noorjahaan; Gavini, Deepti R.; Begum, Gousia (Frontiers in Materials, 2023)
A facile synthetic strategy is demonstrated to generate nickel sulfide quantum dots (Ni3S2). The thus formed Ni3S2 quantum dots are assembled onto exfoliated graphene oxide sheets hydrothermally to form nickel sulfide-graphene oxide nanocomposite material (GO-Ni3S2). The microscopic and spectroscopic characterization of the GO-Ni3S2 nanocomposites revealed the shape, size, crystalline phases, and oxidation states (of elements) of the hybrid material. The GO-Ni3S2 nanocomposites are then coated onto the glassy carbon electrode by drop casting to form GO-Ni3S2@GCE. The modified electrode is then used to detect dopamine and tyrosine simultaneously. The effect of scan rate, analyte concentrations, pH, and interfering agents on the peak current are studied to establish a plausible mechanism for oxidizing dopamine and tyrosine at GO-Ni3S2@GCE. The GO-Ni3S2@GCE is stable for 3 weeks and ten cycles of washing with minimal loss in the peak current in each cycle. Dopamine with a concentration as low as 12 nM can be detected using the GO-Ni3S2@GCE system.